1989
DOI: 10.1042/bj2630301
|View full text |Cite
|
Sign up to set email alerts
|

Plant mitochondrial F1-ATPase. The presence of oligomycin-sensitivity-conferring protein (OSCP)

Abstract: Purified pea (Pisum sativum) cotyledon Fl-ATPase contains six subunits rather than the five usually reported for F1-ATPases. The additional 26.5 kDa (a) subunit is shown by immunoblotting and N-terminal amino acid sequencing to be similar to bovine oligomycin-sensitivity-conferring protein (OSCP). It is concluded that the a subunit of plant mitochondrial Fl-ATPase is the plant OSCP. This OSCP subunit occurs in all mono-and di-cotyledonous species of plants tested (maize, oats, peas, potatoes, sweet potatoes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…Of the three residues which are common in all the relevant parts of the e subunit alignments of Walker et al [18], only proline-53 (in the bovine sequence) is conserved through the two plant mitochondrial tS' sequences. The similarities between the plant mitochondrial tS' and other ATPase subunit sequences show that this subunit is not unique to plant F1-ATPase and confirm an earlier suggestion [11] that the plant tS' subunit is the plant equivalent of the bovine t5 and the chloroplast and bacterial e subunits.…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Of the three residues which are common in all the relevant parts of the e subunit alignments of Walker et al [18], only proline-53 (in the bovine sequence) is conserved through the two plant mitochondrial tS' sequences. The similarities between the plant mitochondrial tS' and other ATPase subunit sequences show that this subunit is not unique to plant F1-ATPase and confirm an earlier suggestion [11] that the plant tS' subunit is the plant equivalent of the bovine t5 and the chloroplast and bacterial e subunits.…”
Section: Methodssupporting
confidence: 83%
“…Confusion exists in the identification of the subunits in the six subunit preparations of plant Fx because these preparations contain two polypeptides in the (5 region, the (5 (Mr 25000-27000) and the 6' (Mr 20000-23000). The 6 subunit of the six-subunit pea ATPase has been identified as the plant oligomycin-sensitivity-conferring protein [11], indicating that the 6' (20 kDa) subunit may be the plant equivalent of the ~ subunit of the mammalian F1-ATPase. However, the 6' (23 kDa) [12].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme was purified 19-fold from submitochondrial particles with a final specific activity of 23 units/mg. This paper was followed by the identification of several of the F]-ATPase subunits (Horak et al, 1987(Horak et al, , 1989a(Horak et al, , 1990 and by functionality studies performed through membrane reconstitution and stability experiments (Horak et al, 1987(Horak et al, , 1988(Horak et al, , 1989b. The pea mitochondrial F,-ATPase has six subunits, a characteristic seen in several other preparations from plants (sweet potato root [Iwasaki andAsahi, 1983, 1985] and turnip [O'Rourke, 1988]).…”
Section: Discussionmentioning
confidence: 99%
“…101, 1993 al., 19851, and spinach leaf [Hamasur and Glaser, 19901). Horak et al (1989aHorak et al ( , 1989b showed that the sixth subunit (termed the 6-subunit by Horak and Packer, 1985) is the oligomycin sensitivity-confemng protein. This subunit is frequently lost from the enzyme preparation when harsh methods are used to liberate the F1 portion from the membrane (Horak et al, 1989b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation